Congenital Lymphocytic Choriomeningitis Virus: When to consider the diagnosis - Anderson, Jacqueline L. (2013)
Lymphocytic Choriomeningitis Virus (LCMV) is a rodent-borne arenavirus that can cause congenital infection affecting the developing central nervous system. When the infection occurs during pregnancy, the virus targets the fetal brain and retina potentially causing ventriculomegaly, hydrocephalus, chorioretinitis, and neurodevelopmental abnormalities. It has been previously suggested that lymphocytic choriomeningitis virus be added to the list of congenital infections currently included in the TORCH acronym (Toxoplasmosis, Rubella, Cytomegalovirus, Herpes, and Syphilis). We present two neonates with antenatally known ventriculomegaly that were diagnosed with congenital lymphocytic choriomeningitis virus infection after birth. In addition to ventriculomegaly, one had non-immune hydrops fetalis and the other had intracranial hemorrhage. In view of the seroprevalence of lymphocytic choriomeningitis Virus (4.7–10%), our findings suggest that screening for congenital lymphocytic choriomeningitis virus infection should be considered in fetuses and newborns with ventriculomegaly as well as other abnormal neuroimaging findings such as intracranial hemorrhage.